2018
DOI: 10.1093/jcag/gwy001
|View full text |Cite
|
Sign up to set email alerts
|

Patient-ly Waiting: A Review of Patient-Centered Access to Inflammatory Bowel Disease Care in Canada

Abstract: Canada has one of the highest prevalence estimates of inflammatory bowel disease (IBD) in the world. Like other chronic illnesses, access to specialist care is required for disease management. Traditionally, access to care is evaluated through wait times (actual access); however, new patient-oriented definitions of access (perceived access) highlight other equally important facets of access to care (e.g., appropriateness). Aim: How does access to gastroenterology speciality care influence disease-related outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Community supports can include community-based allied health professionals with knowledge and expertise in IBD, improved access in the community to nursing support for education, as well as interventions for mental health, nutrition and chronic pain management. The need for community support development for those diagnosed with IBD and their care providers has been well documented ( 2 , 15 , 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…Community supports can include community-based allied health professionals with knowledge and expertise in IBD, improved access in the community to nursing support for education, as well as interventions for mental health, nutrition and chronic pain management. The need for community support development for those diagnosed with IBD and their care providers has been well documented ( 2 , 15 , 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…could prevent new referral delays and redundant testing while allowing more fruitful encounters with IBD specialists. This will allow timely evaluation, diagnosis, and treatment within appropriate therapeutic windows by IBD specialists (Mathias et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…According to Mathias et al (2018) in a retrospective study, 80% of the new patient referrals lacked basic information (e.g., reason for referrals) or pertinent diagnostic studies (e.g., endoscopy reports and imaging studies) resulting in delay of a clinic appointment by an average of 12 weeks. In an effort to make the referral process efficient, an IBD committee recently developed a referral algorithm to guide non-IBD specialists on stratifying new IBD patients by disease risks and referring to the right level of clinician in a timely fashion (Kinnucan et al, 2019).…”
Section: Efficient Referral Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Local data reveal even less favorable patterns of GI follow-ups. In the IBD center in Nova Scotia, canada, the wait time for a new GI consultation averages 184.8 days (Mathias, van Zanten, Kits, Heisler, & Jones, 2018). Additionally, at the project site, a tertiary academic center in Maryland, the preliminary data in July 2019 showed that the average time of next available appointments for 8 gastroenterologists was 71.8 and 78.6 days for new and existing patients with IBD, respectively.…”
Section: Introductionmentioning
confidence: 99%